Catastrophe Insurance Market in the Caribbean Region : Market Failures and Recommendations for Public Sector Interventions - Auffret, Philippe (World Bank, Washington, DC, 2014)
The Caribbean region suffers from a high degree of economic volatility. A history of repeated external and domestic shocks has made economic insecurity a major concern across the region. Of particular concern to all households, especially the poorest segments of the population, is the exposure to shocks that are generated by catastrophic events or natural disasters. The author develops a conceptual framework for risk management and shows that the insurance market for catastrophic risk in the Caribbean region remains a "thin" market characterized by "high" prices and "low" transfer of risk. He analyzes the possible market failures which could explain the lack of development of the catastrophe insurance market. Finally he outlines a set of recommendations for public sector interventions.